SINGLE COMPLETE DENTURE IN MANDIBULAR ARCH OPPOSING NATURAL DENTITION– A CASE REPORT - Kaira, Laxman Singh; Singh, Richa (Journal of Health and Allied Sciences NU, 2013)
Several difficulties are encountered in providing a successful, single complete denture treatment. This case report deals with successful rehabilitation of completely resorbed mandibular ridge opposing a full complement of natural teeth prosthetically incorporating metal denture base in place of the conventional Poly Methyl Methacrylate material to combat the masticatory forces from natural dentition and improve the longevity of the prosthetic rehabilitation, at the same time improving the strength of the mandibular denture base.
Keywords: residual ridge resorption; metal denture base; single complete denture